Evaluation as a comprehensive training practice (ARQUISUR Revista, 2018)
This paper presents contributions on the subject of assessing in Architecture workshops, from the FAU UNLP doctoral research carried out by the authors. In this regard, the research problem is described ("reduction of assessing practices to qualification and accreditation"), general goal ("analyze and describe the intervening variables in assessing didactic modalities used in Architecture teaching, in order to contribute towards its resignification and use as integral training practice") and main hypothesis ("teacher training in key pedagogical aspects related to evaluation promotes its use in integral sense, in promotion of quantitative and qualitative training"). Basic definitions in relation to assessment and workshop logics are described, together with didactic modality of "enchinchada". Methodology and its application through a training teacher practice is described. Concluding with reflections related to the need of stimulating and producing training in key pedagogical aspects towards integral formation for improvement of our university teaching practices.
Keywords: assessment; teaching; integral training; workshop; indicators